Rule of jurisdiction of Article 5.3 Regulation 44/2001 in cases of indirect victims. Commentary of Judgment of the Court, 21 december 2016, Concurrence, C-618/15 - Rodríguez Rodrigo, Juliana (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
In this judgment, the Court answers to a prejudicial question held by French Cour of Cassation, regarding to a litigation on a selective distribution agreement between Samsung and Concurrence. This contract disposes that Concurrence only can resell the Samsung ELITE products through the products on line. For this reason, Samsung ends their relationship and Concurrence bringsan action against it because it says that Amazon also sells these products of Samsung on its webpage. In addition, Concurrence sues Amazon to withdraw the sales of these products because of the damage suffered for them. The prejudicial question is regarding this action for an injunction prohibiting unlawful interference, between Concurrence and Amazon United Kingdom, Amazon Germany, Amazon Spain and Amazon Italy. The Court considers the French jurisdiction has to apply the rule of article 5.3 Regulation 44/2001 –article 7.2 Regulation 1215/2012–, in case of there are damages suffered by Concurrence in France due to sales of Amazon on these webpages situated out of France. Following the Court, in this situation, as the defendant would be Amazon United Kingdom, Amazon Germany, Amazon Spain and Amazon Italy, the French jurisdiction couldn`t be competent by domicile of defendant neither by place where harmful event occurred. It only could be competent by the place of occurred damage.We consider that Concurrence is a indirect victim and, so that, couldn`t apply the article 5.3 Regulation 44/2001 –article 7.2 Regulation 1215/2012– in this case.
Keywords: Selective distribution agreement; Prohibition on online resale; Tort; delict or quasidelict rule of jurisdiction; indirect victim